COMPARISON OF EFFECTIVENESS BETWEEN CELERY JUICE (Apium graveolens L.) AND 2% MICONAZOLE TOWARDS THE GROWTH OF Malassezia furfur - Ronaa Hammada; Witri Pratiwi; Shofa Nur Fauzah; Donny Nauphar; Amanah Amanah (Proceedings of the International Conference on Applied Science and Health, 2018)
Introduction: Pityriasis versicolor is caused by the fungi Malassezia furfur with a worldwide prevalence of 50%, including tropical countries, second only to dermatitis in Indonesia. Pityriasis versicolor is difficult to treat and requires long-term treatment. The disease has high recurrence risk and may cause drug resistance. 2% Miconazole is known to have long-term side effects; therefore, alternative treatment is needed. Several studies suggested that celery (Apium graveolens L.) contains active substances with anti-fungal properties. This paper aims to investigate the comparison of effectiveness between celery juice and 2% Miconazole towards the growth of Malassezia furfur. Methods: This is an in-vitro experimental study with post-test only control group design. The subjects were split into 5 groups which were given celery juice in 10% DMSO with the concentration of 10%, 20%, 30%, 40%, and 50%. A negative control group was given only 10% DMSO and the positive control group was given 2% Miconazole. The data were then analyzed using Kruskall-Wallis followed by Mann-Whitney test. Results: The Kruskall-Wallis test showed all concentration of celery juice had antifungal effect with p=0.000 (p<0.05) and were effective in inhibiting the growth of Malassezia furfur. The Mann-Whitney test showed that the 50% celery concentration was as effective as 2% Miconazole in inhibiting the growth of Malassezia furfur (p=0.495). Conclusion: Celery juice (Apium graveolens L.) was effective in inhibiting the growth of Malassezia furfur with 50% concentration as the most effective concentration.